2022
DOI: 10.3390/ijms23020959
|View full text |Cite
|
Sign up to set email alerts
|

Functional Selectivity of Coumarin Derivates Acting via GPR55 in Neuroinflammation

Abstract: Anti-neuroinflammatory treatment has gained importance in the search for pharmacological treatments of different neurological and psychiatric diseases, such as depression, schizophrenia, Parkinson’s disease, and Alzheimer’s disease. Clinical studies demonstrate a reduction of the mentioned diseases’ symptoms after the administration of anti-inflammatory drugs. Novel coumarin derivates have been shown to elicit anti-neuroinflammatory effects via G-protein coupled receptor GPR55, with possibly reduced side-effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 63 publications
0
22
2
Order By: Relevance
“…The BV-2 cell line is derived from a single cell clone and is immortalized by introducing two oncogenes after a J2 virus infection, possibly affecting some signaling pathways, even if morphology and function are somehow comparable to primary microglia [ 42 ]. Furthermore, the comparison of two different species—mouse for BV-2 cells and rat used for primary microglia cultures in this study—might affect the results, as we have discussed previously due to species-specific differences in receptors, enzymes, and signaling pathways [ 43 ]. Additionally, it has been shown that primary microglia underly individual epigenetic priming, modulating inflammatory responses, and result in different reactions of naive microglia to the same stimulus [ 44 ], delivering another explanation for the differences observed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The BV-2 cell line is derived from a single cell clone and is immortalized by introducing two oncogenes after a J2 virus infection, possibly affecting some signaling pathways, even if morphology and function are somehow comparable to primary microglia [ 42 ]. Furthermore, the comparison of two different species—mouse for BV-2 cells and rat used for primary microglia cultures in this study—might affect the results, as we have discussed previously due to species-specific differences in receptors, enzymes, and signaling pathways [ 43 ]. Additionally, it has been shown that primary microglia underly individual epigenetic priming, modulating inflammatory responses, and result in different reactions of naive microglia to the same stimulus [ 44 ], delivering another explanation for the differences observed.…”
Section: Discussionmentioning
confidence: 99%
“…However, after 12 h, Licochalcone A only showed a significant reduction of TNFα in a concentration of 20 µM, and after 24 h LPS stimulation, the timepoint we used in this study, no significant effects of Licochalcone A on TNFα release were found [ 17 ], contrasting our results. However, again, two different species, and in this case even different types of cells are compared, possibly explaining differences by functional selectivity and species-dependent effects [ 43 ]. Furthermore, both presented studies used 100 times higher doses (1 µg/mL) of LPS for the stimulation of their cell lines and higher total concentrations of Licochalcone A, further hindering a comparison [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Upregulation of GPR55 mRNA expression was also reported in intestinal inflammation [ 173 ]. The overexpression was associated with the development of Crohn’s disease [ 164 , 174 , 175 ]. The upregulation of GPR55 expression may also play a role in obesity [ 176 ].…”
Section: Pharmacogenomics Of Receptorsmentioning
confidence: 99%
“…As discussed before, biased agonism might be responsible for the observed differentiated effects in addition to the different cells or species being used [32]. The role of GPR55 in the regulation of inflammation, therefore, remains the focus of current research.…”
Section: Introductionmentioning
confidence: 99%